The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/774075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered gut microbiota and immunity defines Plasmodium vivax survival in Anopheles stephensi

Abstract: AbstractBlood feeding-enriched gut-microbiota boosts mosquitoes’ anti-Plasmodium immunity. Here, we ask how Plasmodium vivax alters microbiota, anti-Plasmodial immunity and impact tripartite Plasmodium-mosquito-microbiota interactions in the gut lumen. Using a metagenomics analysis, we predominantly detect Elizabethkingia meningitis and Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…gambiae 42 . Our recent study suggests that P. vivax infection restricts gut‐flora proliferation, which consequently facilitates Plasmodium development 34 . In this study, we observed that P. vivax infection not only caused a limited change in the expression of hemocyte FREP13 (Figure 6a) during the late phase but also caused significant downregulation in the midgut during the early phase of infection (Figure 6b).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…gambiae 42 . Our recent study suggests that P. vivax infection restricts gut‐flora proliferation, which consequently facilitates Plasmodium development 34 . In this study, we observed that P. vivax infection not only caused a limited change in the expression of hemocyte FREP13 (Figure 6a) during the late phase but also caused significant downregulation in the midgut during the early phase of infection (Figure 6b).…”
Section: Resultssupporting
confidence: 60%
“…To test this hypothesis, we examined the effect of FREP13 silencing on gut microbiota proliferation following blood‐feeding. Although blood‐meal causes a multifold expansion of gut symbionts within 24 h of blood‐feeding in naïve mosquitoes, 34,48 surprisingly, depletion of FREP13 messenger RNA in the hemocytes causes an initial increase of gut bacteria within 12‐h after blood‐meal, followed by rapid declination and re‐enrichment of the total bacterial population in the gut after 24 or 48 h of blood‐feeding, respectively (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…This genus appears to have a role in increasing iron metabolism necessary for bacterial growth and Plasmodium development (Clark et al, 2014; FIGURE 4 | Bacterial genera identified in Anopheles species by PCR-TTGE. Sharma et al, 2019). Bacterial microbiota in Anopheles and their effects on the development of Plasmodium parasites as a potential means of controlling malaria transmission have been reported in various Anopheles species, but the precise mechanisms of activity remain poorly understood (Dong et al, 2009;Meister et al, 2009;Abdul-Ghani et al, 2012;Gendrin and Christophides, 2013;Minard et al, 2013;Hughes et al, 2014;Sharma et al, 2014;Villegas and Pimenta, 2014;Romoli and Gendrin, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…gambiae (Boissière et al, 2012;Ngwa et al, 2013). Sharma et al (2019) reported an interesting microbial interaction and immune modulation, whereby the presence of P. vivax in An. stephensi provoked a metabolic alteration of the availability of iron and nutritional physiology required for ideal bacterial growth resulting in a reduction of the microbiota present in the midgut, particularly the predominant bacteria Elizabethkingia and Pseudomonas.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi mosquitoes were fed on the P. vivax infected patient's blood (~2% gametocytemia) through preoptimized artificial membrane feeding assay (34). The confirmation of the P. vivax infection was done by staining the midgut with 5% mercurochrome to visualize the oocysts after 4 days postinfection (DPI), as described earlier (34). After confirmation, ~20-25 mosquitos' Salivary gland dissected at 9-12DPI and 12-14DPI, respectively.…”
Section: Sample Collection and Rna Extractionmentioning
confidence: 99%